Development of bio-based active packaging material evaluating grapefruit seed and grape seed extract as antimicrobials - Cerón G., Mirella M. (Zamorano: Escuela Agrícola Panamericana, 2020., 2020)
New trends related to consumers in food packaging include the preference for green and sustainable biopolymers. This study determined a formulation and process flow diagram for the development of an active packaging based on Pullulan and Polylactic acid (PLA), incorporating grape seed and grapefruit seed extract as antimicrobials. Physical, mechanical, and antimicrobial properties of the created film were evaluated. Two completely randomized design with two variables to optimize film formulations was used. The independent variables were grape seed and grapefruit seed extract in two concentrations (1 and 5%). Three replicates were performed for each treatment, for a total of 24 experimental units for each statistical analysis. Evaluations performed were thickness, ultimate tensile strength (UTS), elongation at break (EL), elasticity (YM), color (L*, a*, b*), and antimicrobial activity. Results for mechanical properties indicated that there was an interaction between the extract and concentrations, meaning that, depending the concentration of the extract, the mechanical properties will change. In contrast, antimicrobial properties Listeria monocytogenes, Salmonella Infantis and Seftenberg; Escherichia coli O26 and O157:H7 are susceptible to films with grapefruit seed extract. However, the inhibitory effect on bacteria growth will remain the same regardless of concentration. This point out that Pullulan with grapefruit seed extract can be used as an active packaging, inhibiting Gram-positive (Listeria monocytogenes) and Gram-negative (Salmonella spp and Escherichia coli) foodborne pathogens.